STIMULASI PERKEMBANGAN MOTORIK ANAK USIA DINI MELALUI KEGIATAN SENAM DAN MEMBATIK TIE-DYE: PERPEKTIF PENDIDIKAN JASMANI DAN PENDIDIKAN ANAK USIA DINI - Yunisa Rahmah; Iip Fajriani; Siti Mariah; Laxmi Permata Sari Suardi (Cakrawala Pedagogik, 2025)
Physical development in early childhood plays a crucial role in supporting both gross and fine motor skills. Various physical activities can attract children's interest, encourage them to be more active, enhance their social abilities, and instill healthy habits. This study aims to examine children's physical development through gymnastic activities and a tie-dye (batik lipat) project. The research applied a descriptive qualitative method, with data collected through participant observation, documentation, interviews, and direct observation. The findings indicate that gymnastics can improve children’s gross motor skills, while tie-dye activities, involving tasks such as folding, tying, and coloring, contribute to fine motor development. Additionally, active participation in these activities positively affects children’s self-confidence and discipline. The study concludes that combining physical and creative activities provides optimal benefits for early childhood physical growth.